Furthering 4R Nutrient Stewardship - Bruulsema, Tom; Cakmak, Ismail; Dobermann, Achim; Gerard, Bruno G.; Majumdar, Kaushik; McLaughlin, Michael; Reidsma, Pytrik; Vanlauwe, Bernard; Wollenberg, Eva Karoline; Zhang, Fusuo; Zhang, Xin (2022)
Future implementations of 4R Nutrient Stewardship need to integrate with changing farming objectives that support a wider range of sustainability outcomes. The new paradigm for Responsible Plant Nutrition provides perspective for such integration. We suggest changes to align it with future farming systems that intensify production, improve human nutrition, protect and enhance biodiversity, shrink environmental and carbon footprints, and make nutrient flows more circular.